Remediasi Tanah Tercemar Timbal dan Kadmium Menggunakan Fly Ash dan Bahan Organik - Ginting, Ina Febria; Darmawan; Indriyati, Lilik Tri (Departemen Ilmu Tanah dan Sumberdaya Lahan, Fakultas Pertanian, IPB University, 2024)
Agricultural soils that are close to industrial areas are prone to be polluted by lead (Pb) and cadmium (Cd) caused by industrial waste. Soil remediation is a method to clean the soil from pollutant materials. Utilizing fly ash and organic matter is a way to reduce levels of Pb and Cd pollution in the soil. This research was conducted to study the effect of ameliorants on reducing the availability of Pb and Cd in soil. The greenhouse experiment was carried out using a randomized block design with the application of 3 types of ameliorants, namely fly ash, chicken manure, and cow manure. The experimental design was prepared with 2 dose levels, namely C: control; F1: 450g; F2: 600g; A1: 75g; A2: 105g; S1: 105g; S2: 135g; FAS1: 450 g+75 g+105 g; FAS2: 600g+105g+135g. Each treatment was repeated 3 times to obtain 27 experimental units. The experimental results showed that the effect of the treatment of fly ash, chicken manure, and cow manure significantly increased soil pH, KB, C-organic, and exchangeable bases as well as reduced levels of availability of Pb and Cd compared to controls. The use of single fly ash (F1 and F2) reduces the availability of Pb in the soil, while the available Cd decreased in the application of a combination of fly ash with chicken and cow manure (FAS1 and FAS2). The application of fly ash alone was able to reduce the availability of Pb and Cd which was higher than of chicken manure and cow manure alone. However, the provision of fly ash has not been able to increase the growth of kale plants. Keywords: Cd, fly ash, chicken manure, cow manure, Pb, remediation